2020
DOI: 10.21203/rs.3.rs-19893/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Salivary cytokines in children with nephrotic syndrome versus healthy children: a comparative study

Abstract: Background: The aims of this study were to compare salivary cytokines and total protein, between children with nephrotic syndrome and healthy children; and to examine whether saliva parameters can differentiate between steroid sensitivity and resistance, and between disease remission and relapse. Methods: Twenty-seven children with nephrotic syndrome were classified according to steroid sensitivity and resistance, and disease remission and relapse. Twenty healthy children served as controls. Whole saliva sampl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“… 28 A few other reports have identified cytokines in plasma, urine, and saliva as markers of persistence of proteinuria or SRNS in childhood NS. 13 A Brazilian study compared peripheral blood leukocytes and their intracellular cytokines in post-therapy samples from 44 pediatric patients, classified as having persistent proteinuria (partial remission) versus low proteinuria (complete remission). These investigators identified higher levels of inflammatory markers with persistent proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 A few other reports have identified cytokines in plasma, urine, and saliva as markers of persistence of proteinuria or SRNS in childhood NS. 13 A Brazilian study compared peripheral blood leukocytes and their intracellular cytokines in post-therapy samples from 44 pediatric patients, classified as having persistent proteinuria (partial remission) versus low proteinuria (complete remission). These investigators identified higher levels of inflammatory markers with persistent proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…To try to better identify those patients highly unlikely to respond to GC, and thus avoid its unnecessary toxicity, a few studies have tried to identify urinary, plasma, and salivary biomarkers for SRNS in children using cytokine profiling and omics approaches such as proteomics, metabolomics, and transcriptomics. 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 As a result, recently T lymphocytes expressing inflammatory cytokines and macrophage migration inhibitory factor in plasma, and MCP-1 in urine have been implicated in persistent proteinuria and SRNS in childhood NS. 8 , 19 , 20 However, despite these efforts, we still lack understanding of the molecular mechanisms regulating GC resistance in NS, and there remain no plasma or urine biomarkers that have been validated to reliably predict GC resistance in NS prior to initiation of GC therapy.…”
mentioning
confidence: 99%
“…iNS is characterized by complex abnormalities in blood tests and treatment by steroids, immunosuppressants or cytostatics, and dietary regimens, which may be reflected in the saliva composition. Unfortunately, we could not compare our results with those of others because data in the literature are scarce and concern the excretion of endogenous proteins (albumin, transferrin, IgG1, and IgG4) [ 24 ], salivary cortisol concentration [ 25 ] and salivary cytokines [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, undisturbed salivary gland activity could be suggested. Polak et al [ 26 ] found a lower total protein concentration in the saliva of children with steroid-sensitive nephrotic syndrome than in the control group.…”
Section: Discussionmentioning
confidence: 99%